Preparation method and application of synergistic flame retardant
By combining alumina with high crystalline boehmite and mixing it with low crystalline boehmite to form a boehmite/alumina composite, the problem of high crystalline boehmite aggregation in plastics is solved and the flame retardant performance is improved.
Patent Information
- Application Number
- CN202411782546.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-05
AI Technical Summary
As a synergistic flame retardant, high-crystalline boehmite is prone to aggregation in plastics, affecting the flame retardant performance.
By combining alumina with high crystalline boehmite and mixing it with low crystalline boehmite, boehmite/alumina composite is formed under ultrasound to avoid aggregation.
The aggregation of boehmite/alumina composite is effectively prevented, the flame retardant performance is improved, and heat exchange is blocked by forming a dense carbon layer.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a preparation method and application of a synergistic flame retardant. Background Art
[0002] Flame retardancy is one of the important properties of automotive interior and exterior trims, plastic housings, etc. There are many ways to improve the flame retardancy of polymers. In current technology, the flame retardancy of plastics is improved by adding flame retardants and / or synergistic flame retardants to plastics.
[0003] In the current technology, boehmite is usually used as a synergistic flame retardant, because boehmite is divided into two categories, namely high crystallinity boehmite and low crystallinity boehmite. Among them, high crystallinity boehmite is a layered crystal structure, each layer is composed of AlO6 octahedrons, and the center of the octahedron is composed of a double-layer structure formed by positively charged Al3+. The surface of the layered structure contains a large number of hydroxyl groups, and the layers are connected by hydrogen bonds between hydroxyl groups to form an ordered layered structure. At the same time, it has a low specific surface area and complete grains, and is used in the field of flame retardants. Low crystallinity boehmite is used in the field of catalyst carriers and adsorption because of its large specific surface area and high porosity. However, high crystallinity boehmite has a small specific surface area. Although it is used in the field of flame retardants, it will aggregate in plastics, which affects the flame retardant properties of plastics. Summary of the invention
[0004] The object of the present invention is to provide a preparation method and application of a synergistic flame retardant to solve the problems existing in the above-mentioned background technology due to the use of high-crystallinity boehmite as a synergistic flame retardant.
[0005] To achieve the above objectives, this application is implemented through the following technical solutions:
[0006] A method for preparing a synergistic flame retardant comprises the following steps:
[0007] S1. Weigh a certain amount of basic aluminum chloride, potassium hydroxide, ether, and deionized water, add them into a reaction vessel, and react at 60-80° C. for 3-5 hours to obtain solution A;
[0008] S2, filtering solution A, washing, drying, and then calcining at 720-780°C for 10-12h to obtain alumina;
[0009] S3, weighing a certain amount of high crystallinity boehmite, grinding it into powder, and passing it through a 500-mesh sieve to obtain high crystallinity boehmite powder; weighing a certain amount of low crystallinity boehmite, grinding it into powder, and passing it through a 350-mesh sieve to obtain low crystallinity boehmite powder;
[0010] S4, weigh a certain amount of alumina, high crystallinity boehmite powder, ether, and deionized water, add them to a reaction vessel, react at 60-80° C. for 6-8 hours, and obtain solution B;
[0011] S5, filtering solution B, washing, and placing in a vacuum drying oven at 60-80° C. for 8-12 hours to obtain a high-crystallinity boehmite / alumina composite;
[0012] S6, grinding the high crystallinity boehmite / alumina composite into powder, and passing through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder;
[0013] S7, adding a certain amount of high crystallinity boehmite / alumina composite powder, low crystallinity boehmite powder, ether, and deionized water into a reaction dish, and subjecting the mixture to ultrasonic reaction at 60-80° C. for 6-8 hours to obtain solution C;
[0014] S8. Filter solution C, wash it, and place it in a vacuum drying oven at 60-80° C. for 8-12 hours to obtain a synergistic flame retardant.
[0015] Furthermore, in step S1, the mass ratio of basic aluminum chloride, potassium hydroxide, ether and deionized water is (20-30): (16-24): (30-36): (62-72).
[0016] Furthermore, in step S4, the mass ratio of alumina, high crystallinity boehmite powder, ether and deionized water is (8-12): (40-50): (50-60): (70-90).
[0017] Furthermore, in step S7, the mass ratio of high crystallinity boehmite / alumina composite powder, low crystallinity boehmite powder, ether and deionized water is: (5-10): (30-50): (50-60): (90-100).
[0018] Furthermore, the ultrasonic reaction in step S7 is 30 KHz.
[0019] Furthermore, in step S8, the mass ratio of high crystallinity boehmite to low crystallinity boehmite is 1:2-1:5.
[0020] An application, use of the synergistic flame retardant prepared by any of the above items in thermoplastic composite materials.
[0021] Furthermore, a thermoplastic composite material is composed of the following components by weight: 90-110 parts of thermoplastic, 16-18 parts of decabromodiphenylethane, 4-6 parts of synergistic flame retardant, and 0.1-0.5 parts of antioxidant.
[0022] Furthermore, the thermoplastic plastic composite material is one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate, and polyamide 6.
[0023] Furthermore, the antioxidant is one of 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)ethyl propionate], 2,6-di-tert-butyl-p-cresol and 4,6-bis(octylthiomethyl)-o-cresol, or a mixture of several thereof.
[0024] The beneficial effects of the present invention are:
[0025] In the present technical scheme, the prepared alumina is first compounded with high-crystallinity boehmite and then mixed with porous low-crystallinity boehmite. Under the action of ultrasound, part of the high-crystallinity boehmite / alumina complex enters into the pores of the low-crystallinity boehmite to form a boehmite / alumina complex. When applied to thermoplastic plastic materials, part of the thermoplastic plastic materials also enter into the pores of the low-crystallinity boehmite, thereby preventing the aggregation of the boehmite / alumina complex. When combustion occurs, the thermoplastic forms a denser carbon layer through the framework of the boehmite / alumina complex, thereby blocking heat exchange and improving flame retardant properties. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is described in detail below through examples. The following examples are merely exemplary and can only be used to explain and illustrate the technical solution of the present invention, but cannot be construed as limiting the technical solution of the present invention.
[0027] In the following examples of the present application, the raw materials, reagents, equipment, etc. involved, unless otherwise specified, can be obtained by those skilled in the art through commercial channels.
[0028] Preparation Example 1
[0029] (1) Weigh 200 g of basic aluminum chloride, 160 g of potassium hydroxide, 300 g of ether, and 620 g of deionized water, add them to a reaction vessel, and react at 60° C. for 3 h to obtain solution A.
[0030] (2) Solution A is filtered, washed, dried, and then calcined at 720°C for 10 hours to obtain alumina.
[0031] (3) Weigh a certain amount of high crystallinity boehmite, grind it into powder in a crucible, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite powder. Weigh a certain amount of low crystallinity boehmite, grind it into powder, and pass it through a 350-mesh sieve to obtain low crystallinity boehmite powder.
[0032] (4) Weigh 80 g of alumina, 400 g of high-crystallinity boehmite powder, 500 g of ether, and 700 g of deionized water, add them into a reaction vessel, and react at 60 °C for 6 h to obtain solution B.
[0033] (5) Solution B was filtered, washed, and placed in a vacuum drying oven at 60°C for 8 hours to obtain a high-crystallinity boehmite / alumina composite.
[0034] (6) Grind the high crystallinity boehmite / alumina composite into powder, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder.
[0035] (7) Weigh 50 g of high crystallinity boehmite / alumina composite powder, 300 g of low crystallinity boehmite powder, 500 g of ether, and 900 g of deionized water, add them into a reaction vessel, and perform ultrasonic reaction at 60°C and 30 kHz for 6 h to obtain solution C.
[0036] (8) Solution C was filtered, washed, and placed in a vacuum drying oven at 60°C for 8 h to obtain a synergistic flame retardant M1.
[0037] Application Example 1
[0038] (1) Weigh 90 parts of PP, 16 parts of decabromodiphenylethane, 4 parts of synergistic flame retardant M1, and 0.1 parts of 2,6-di-tert-butyl-p-cresol, mix and stir to obtain a mixture.
[0039] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material X1.
[0040] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0041] Comparative Example 1
[0042] (1) Weigh 90 parts of PP, 16 parts of decabromodiphenylethane, 4 parts of antimony trioxide, and 0.1 parts of 2,6-di-tert-butyl-p-cresol, mix and stir to obtain a mixture.
[0043] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.
[0044] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0045] The performance data of the PP composite materials prepared in the above Application Example 1 and Comparative Example 1 are shown in the following table:
[0046]
[0047] It can be seen from the above table that the flame retardant property of X1 is better than that of D1, which indicates that after adding the synergistic flame retardant M1 of the present invention, the flame retardant property of PP is better.
[0048] Preparation Example 2
[0049] (1) Weigh 300 g of basic aluminum chloride, 240 g of potassium hydroxide, 360 g of ether, and 720 g of deionized water, add them to a reaction vessel, and react at 80° C. for 5 h to obtain solution A.
[0050] (2) Solution A is filtered, washed, dried, and then calcined at 780°C for 12 hours to obtain alumina.
[0051] (3) Weigh a certain amount of high crystallinity boehmite, grind it into powder in a crucible, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite powder. Weigh a certain amount of low crystallinity boehmite, grind it into powder, and pass it through a 350-mesh sieve to obtain low crystallinity boehmite powder.
[0052] (4) Weigh 80 g of alumina, 400 g of high-crystallinity boehmite powder, 500 g of ether, and 700 g of deionized water, add them into a reaction vessel, and react at 80° C. for 8 h to obtain solution B.
[0053] (5) Solution B was filtered, washed, and placed in a vacuum drying oven at 80°C for 12 hours to obtain a high-crystallinity boehmite / alumina composite.
[0054] (6) Grind the high crystallinity boehmite / alumina composite into powder, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder.
[0055] (7) Weigh 80 g of high crystallinity boehmite / alumina composite powder, 400 g of low crystallinity boehmite powder, 560 g of ether, and 960 g of deionized water, add them into a reaction vessel, and react at 80° C. and 30 kHz for 8 h to obtain solution C.
[0056] (8) Solution C was filtered, washed, and placed in a vacuum drying oven at 80°C for 12 h to obtain a synergistic flame retardant M2.
[0057] Application Example 2
[0058] (1) Weigh 110 parts of PBT, 18 parts of decabromodiphenylethane, 6 parts of synergistic flame retardant M2, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, 0.2 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, and 0.2 parts of antioxidant 4,6-di(octylthiomethyl)-o-cresol, mix and stir evenly to obtain a mixture.
[0059] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material X2.
[0060] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 300r / min.
[0061] Comparative Example 2
[0062] (1) Weigh 110 parts of PBT, 18 parts of decabromodiphenylethane, 6 parts of antimony trioxide, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, 0.2 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, and 0.2 parts of antioxidant 4,6-di(octylthiomethyl)-o-cresol, mix and stir evenly to obtain a mixture;
[0063] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D2.
[0064] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 300r / min.
[0065] The performance data of the PBT composite materials prepared in the above Application Example 2 and Comparative Example 2 are shown in the following table:
[0066]
[0067] It can be seen from the above table that the flame retardant performance of X2 is better than that of D2, which means that after adding the synergistic flame retardant M2 of the present invention, the flame retardant performance of PBT is better.
[0068] Preparation Example 3
[0069] (1) Weigh 250 g of basic aluminum chloride, 200 g of potassium hydroxide, 330 g of ether, and 670 g of deionized water, add them to a reaction vessel, and react at 70° C. for 4 h to obtain solution A.
[0070] (2) Solution A is filtered, washed, dried, and then calcined at 750°C for 11 hours to obtain alumina.
[0071] (3) Weigh a certain amount of high crystallinity boehmite, grind it into powder in a crucible, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite powder. Weigh a certain amount of low crystallinity boehmite, grind it into powder, and pass it through a 350-mesh sieve to obtain low crystallinity boehmite powder.
[0072] (4) Weigh 100 g of alumina, 450 g of high-crystallinity boehmite powder, 550 g of ether, and 800 g of deionized water, add them into a reaction vessel, and react at 70° C. for 7 h to obtain solution B.
[0073] (5) Solution B was filtered, washed, and placed in a vacuum drying oven at 70°C for 10 h to obtain a high-crystallinity boehmite / alumina composite.
[0074] (6) Grind the high crystallinity boehmite / alumina composite into powder, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder.
[0075] (7) Weigh 50 g of high crystallinity boehmite / alumina composite powder, 150 g of low crystallinity boehmite powder, 300 g of ether, and 500 g of deionized water, add them into a reaction vessel, and react with ultrasound at 70°C and 30 kHz for 10 h to obtain solution C.
[0076] (8) Solution C was filtered, washed, and placed in a vacuum drying oven at 70°C for 10 h to obtain a synergistic flame retardant M3.
[0077] (1) Weigh 100 parts of PE, 17 parts of decabromodiphenylethane, 5 parts of synergistic flame retardant M3, 0.1 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, and 0.2 parts of antioxidant 2,6-di-tert-butyl-p-cresol, mix and stir evenly to obtain a mixture.
[0078] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material X3.
[0079] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0080] Comparative Example 3
[0081] (1) Weigh 100 parts of PE, 17 parts of decabromodiphenylethane, 5 parts of antimony trioxide, 0.1 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, and 0.2 parts of antioxidant 2,6-di-tert-butyl-p-cresol, mix and stir evenly to obtain a mixture;
[0082] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D3.
[0083] The performance data of the PE composite materials prepared in the above Application Example 3 and Comparative Example 3 are shown in the following table:
[0084]
[0085] It can be seen from the above table that the flame retardant property of X3 is better than that of D3, which means that after adding the synergistic flame retardant M3 of the present invention, the flame retardant property of PE is better.
[0086] Preparation Example 4
[0087] (1) Weigh 235 g of basic aluminum chloride, 195 g of potassium hydroxide, 335 g of ether, and 705 g of deionized water, add them to a reaction vessel, and react at 75° C. for 3.5 h to obtain solution A.
[0088] (2) Solution A was filtered, washed, dried, and then calcined at 75°C for 11.5 hours to obtain alumina.
[0089] (3) Weigh a certain amount of high crystallinity boehmite, grind it into powder in a crucible, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite powder. Weigh a certain amount of low crystallinity boehmite, grind it into powder, and pass it through a 350-mesh sieve to obtain low crystallinity boehmite powder.
[0090] (4) Weigh 105 g of alumina, 435 g of high-crystallinity boehmite powder, 565 g of ether, and 765 g of deionized water, add them into a reaction vessel, and react at 75° C. for 7.5 h to obtain solution B.
[0091] (5) Solution B was filtered, washed, and placed in a vacuum drying oven at 75°C for 11.5 hours to obtain a high-crystallinity boehmite / alumina composite.
[0092] (6) Grind the high crystallinity boehmite / alumina composite into powder, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder.
[0093] (7) Weigh 50 g of high crystallinity boehmite / alumina composite powder, 300 g of low crystallinity boehmite powder, 350 g of ether, and 600 g of deionized water, add them into a reaction vessel, and react with ultrasound at 50°C and 30 kHz for 10 h to obtain solution C.
[0094] (8) Solution C was filtered, washed, and placed in a vacuum drying oven at 75°C for 10 h to obtain synergistic flame retardant M4.
[0095] Application Example 4
[0096] (1) Weigh 98.5 parts of PA6, 16.6 parts of decabromodiphenylethane, 4.8 parts of synergistic flame retardant M4, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, and 0.2 parts of antioxidant 4,6-di(octylthiomethyl)-o-cresol, mix and stir evenly to obtain a mixture;
[0097] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material X4.
[0098] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 230°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 250°C, and the screw speed is 320r / min.
[0099] Comparative Example 4
[0100] (1) Weigh 98.5 parts of PA6, 16.6 parts of decabromodiphenylethane, 4.8 parts of antimony trioxide, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, and 0.2 parts of antioxidant 4,6-di(octylthiomethyl)-o-cresol, mix and stir evenly to obtain a mixture.
[0101] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D4.
[0102] The performance data of the PA6 composite materials prepared in the above Application Example 4 and Comparative Example 4 are shown in the following table:
[0103]
[0104] It can be seen from the above table that the flame retardant property of X4 is better than that of D4, which indicates that after adding the synergistic flame retardant of the present invention, the flame retardant property of PA6 is better.
[0105] Preparation Example 5
[0106] (1) Weigh 225 g of basic aluminum chloride, 195 g of potassium hydroxide, 345 g of ether, and 695 g of deionized water, add them to a reaction vessel, and react at 65° C. for 4.5 h to obtain solution A.
[0107] (2) Solution A was filtered, washed, dried, and then calcined at 65°C for 10.5 hours to obtain alumina.
[0108] (3) Weigh a certain amount of high crystallinity boehmite, grind it into powder in a crucible, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite powder. Weigh a certain amount of low crystallinity boehmite, grind it into powder, and pass it through a 350-mesh sieve to obtain low crystallinity boehmite powder.
[0109] (4) Weigh 115 g of alumina, 465 g of high-crystallinity boehmite powder, 555 g of ether, and 735 g of deionized water, add them into a reaction vessel, and react at 78.5° C. for 7.5 h to obtain solution B.
[0110] (5) Solution B was filtered, washed, and placed in a vacuum drying oven at 69°C for 10.5 hours to obtain a high-crystallinity boehmite / alumina composite.
[0111] (6) Grind the high crystallinity boehmite / alumina composite into powder, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder.
[0112] (7) Weigh 50 g of high crystallinity boehmite / alumina composite powder, 350 g of low crystallinity boehmite powder, 400 g of ether, and 740 g of deionized water, add them into a reaction vessel, and react at 65°C and 30 kHz for 10 h to obtain solution C.
[0113] (8) Solution C was filtered, washed, and placed in a vacuum drying oven at 65°C for 10 h to obtain a synergistic flame retardant M5.
[0114] (1) Weigh 99 parts of PS, 17.8 parts of decabromodiphenylethane, 5.8 parts of synergistic flame retardant M5, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, and 0.1 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, mix and stir evenly to obtain a mixture;
[0115] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material X5.
[0116] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 160°C, the temperature of the second temperature zone is 200°C, the temperature of the third temperature zone is 200°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 200°C, the head temperature of the twin-screw extruder is 200°C, and the screw speed is 280r / min.
[0117] Comparative Example 5
[0118] (1) Weigh 99 parts of PS, 17.8 parts of decabromodiphenylethane, 5.8 parts of antimony trioxide, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, and 0.1 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, mix and stir evenly to obtain a mixture;
[0119] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D5.
[0120] The performance data of the PS composite materials prepared in the above Application Example 5 and Comparative Example 5 are shown in the following table:
[0121]
[0122] It can be seen from the above table that the flame retardant property of X5 is better than that of D5, which means that after adding the synergistic flame retardant M5 of the present invention, the flame retardant property of PS is better.
[0123] The above disclosures are only a few specific embodiments of the present application, but the present application is not limited thereto, and any changes that can be conceived by those skilled in the art should fall within the protection scope of the present application.
Claims
1. A method for preparing a synergistic flame retardant, characterized in that: The following steps are involved: S1. Weigh a certain amount of basic aluminum chloride, potassium hydroxide, ether, and deionized water, add them into a reaction vessel, and react at 60-80° C. for 3-5 hours to obtain solution A; S2, filtering solution A, washing, drying, and then calcining at 720-780°C for 10-12h to obtain alumina; S3, weighing a certain amount of high crystallinity boehmite, grinding it into powder, and passing it through a 500-mesh sieve to obtain high crystallinity boehmite powder; weighing a certain amount of low crystallinity boehmite, grinding it into powder, and passing it through a 350-mesh sieve to obtain low crystallinity boehmite powder; S4, weigh a certain amount of alumina, high crystallinity boehmite powder, ether, and deionized water, add them to a reaction vessel, react at 60-80° C. for 6-8 hours, and obtain solution B; S5, filtering solution B, washing, and placing in a vacuum drying oven at 60-80° C. for 8-12 hours to obtain a high-crystallinity boehmite / alumina composite; S6, grinding the high crystallinity boehmite / alumina composite into powder, and passing the powder through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder; S7, adding a certain amount of high crystallinity boehmite / alumina composite powder, low crystallinity boehmite powder, ether, and deionized water into a reaction dish, and subjecting the mixture to ultrasonic reaction at 60-80° C. for 6-8 hours to obtain solution C; S8. Filter solution C, wash it, and place it in a vacuum drying oven at 60-80° C. for 8-12 hours to obtain a synergistic flame retardant.
2. The method for preparing a synergistic flame retardant according to claim 1, characterized in that: In step S1, the mass ratio of basic aluminum chloride, potassium hydroxide, ether and deionized water is (20-30): (16-24): (30-36): (62-72).
3. The method for preparing a synergistic flame retardant according to claim 1, characterized in that: In step S4, the mass ratio of alumina, high crystallinity boehmite powder, ether and deionized water is (8-12): (40-50): (50-60): (70-90).
4. The method for preparing a synergistic flame retardant according to claim 1, characterized in that: In step S7, the mass ratio of high crystallinity boehmite / alumina composite powder, low crystallinity boehmite powder, ether and deionized water is: (5-10): (30-50): (50-60): (90-100).
5. The method for preparing a synergistic flame retardant according to claim 1, characterized in that: The ultrasonic reaction in step S7 is 30 KHz.
6. The method for preparing a synergistic flame retardant according to claim 1, characterized in that: In step S8, the mass ratio of high crystallinity boehmite to low crystallinity boehmite is 1:2-1:
5.
7. An application, characterized in that: Use of the synergistic flame retardant prepared according to any one of claims 1 to 6 in thermoplastic composite materials.
8. The use according to claim 7, characterized in that: The thermoplastic composite material consists of the following components by weight: 90-110 parts of thermoplastic plastic, 16-18 parts of decabromodiphenylethane, 4-6 parts of synergistic flame retardant, and 0.1-0.5 parts of antioxidant.
9. The use according to claim 8, characterized in that: The thermoplastic plastic composite material is one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate and polyamide 6.
10. The use according to claim 8, characterized in that: The antioxidant is one of 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)ethyl propionate], 2,6-di-tert-butyl-p-cresol and 4,6-bis(octylthiomethyl)-o-cresol or a mixture of several thereof.
Citation Information
Patent Citations
Thermally-conductive and flame-retardant composite filler and preparation method thereof
CN109232990A
Boehmite and preparation method thereof
CN118206143A
An improved process for the preparation of dispersible boehmite alumina
IN201941012516A
Method for the production of a finely crystalline boehmite and application of said boehmite as flame retardant in plastics
US20070217993A1